Investigating the role of chain and linker length on the catalytic activity of an H2 production catalyst containing a β-hairpin peptide. Issue 11 (2nd July 2016) - Reback, Matthew L.; Ginovska, Bojana; Buchko, Garry W.; Dutta, Arnab; Priyadarshani, Nilusha; Kier, Brandon L.; Helm, Monte L.; Raugei, Simone; Shaw, Wendy J.
Abstract: Building on our recent report of an active H2 production catalyst [Ni(P Ph 2 N Prop–peptide )2 ] 2+ (Prop =  para -phenylpropionic acid, peptide (R10) = WIpPRWTGPR-NH2, p = D-proline and P2 N = 1-aza-3, 6-diphosphacycloheptane) that contains structured β-hairpin peptides, here we investigate how H2 production is effected by: (1) the length of the hairpin (8 or 10 residues) and (2) limiting the flexibility between the peptide and the core complex by altering the length of the linker: para -phenylpropionic acid (three carbons) or para -benzoic acid (one carbon). Reduction of the peptide chain length from 10 to 8 residues increases or maintains the catalytic current for H2 production for all complexes, suggesting a non-productive steric interaction at longer peptide lengths. While the structure of the hairpin appears largely intact for the complexes, NMR data are consistent with differences in dynamic behavior which may contribute to the observed differences in catalytic activity. Molecular dynamics simulations demonstrate that complexes with a one-carbon linker have the desired effect of restricting the motion of the hairpin relative to the complex; however, the catalytic currents are significantly reduced compared to complexes containing a three-carbon linker as a result of the electron withdrawing nature of the –COOH group. These results demonstrate the complexity and interrelated nature of the outer coordination sphere on catalysis. Abstract :